2009
DOI: 10.3109/01443610903229598
|View full text |Cite
|
Sign up to set email alerts
|

Predicting poor perinatal outcome in women who present with decreased fetal movements

Abstract: Maternal perception of decreased fetal movements (DFM) is associated with increased incidence of stillbirth and intrauterine growth restriction. We hypothesised that clinical assessment of women perceiving DFM may identify patients at highest risk of poor perinatal outcome. This was a retrospective study of 203 patients presenting to the obstetric triage service with DFM. Information on obstetric and past medical history, the current presentation with DFM and the outcome of pregnancy was collected. Using multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 19 publications
8
80
2
Order By: Relevance
“…A growing number of studies have confirmed a correlation between episodes of RFM and stillbirth. 1 RFM has been shown to occur in up to 15% of pregnancies. 2 Women who have a stillbirth note a reduction in fetal movement prior to diagnosis in up to 55%.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of studies have confirmed a correlation between episodes of RFM and stillbirth. 1 RFM has been shown to occur in up to 15% of pregnancies. 2 Women who have a stillbirth note a reduction in fetal movement prior to diagnosis in up to 55%.…”
Section: Introductionmentioning
confidence: 99%
“…It reduces the risk of stillbirth, fetal growth restriction, fetal distress and perinatal mortality. Furthermore, the maternal-fetal attachment is increased by fetal movements' perception (11,20,21) . Health care providers have long acknowledged the importance of maternally perceived fetal movements, but continue to DOI: 10.9790/1959-060207107119 www.iosrjournals.org 117 | Page under investigate the maternal perception of fetal activity to date (22,23) .…”
Section: Discussionmentioning
confidence: 99%
“…While, excessive movements provide reassurance of fetal well-being and oxygenation (16,29,30) . On the other hand, several researchers indicated that women who perceive a reduction in fetal movements will have a normal outcome to their pregnancy (4,11,31) . Regarding knowledge of fetal movement, the present study revealed that the majority of the studied women expressed that it is important to feel the fetal movements, and three-quarters of them reasoned that this is an indication that the baby is alive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the perception of reduced FM persists, consideration should be given to other causes such as fetal structural anomalies (4.3%), anaemia or feto-maternal haemorrhage. There is little evidence how to manage these pregnancies, however women who present on two or more occasions with reduced FM are at increased risk of poor perinatal outcome compared with those who attend only once (OR 1.92; 95% CI 1.21 -2.02) (O'Sullivan et al, 2009). A practical approach would be to perform ultrasound assessment to rule out SGA, structural anomalies and oligo-or polyhydramnios and invite the woman for daily CTGs until mother and clinician are reassured.…”
Section: Management Of Second and Subsequent Presentationsmentioning
confidence: 99%